Desorption Of Te Capping Layer From Znte (100): Auger Spectroscopy, Low-energy Electron Diffraction And Scanning Tunneling Microscopy - Sossoe, K. K.; Dzagli, M. M.; Sylla, A.; Grandidier, B.; Mohou, M. A.; Zoueu, T. J.; Toure, S. (University of Eloued جامعة الوادي, 2016)
The influence of the annealing temperature to desorb a protective Te capping layer of the zinc telluride (ZnTe (100)) surface was investigated. The surface reconstruction of the ZnTe (100) upon the removal of a Te capping layer grown by the molecular beam epitaxy was characterized by different methods. Auger spectroscopy brought out the chemical composition of the surface before and after annealing; the Low-energy electron diffraction (LEED) gave information about the crystallographic structure. The surface crystallographic configurations of tellurium Te (c (2x2)) and Te (c (2x1)) are confirmed by scanning tunneling microscopy (STM). Such a study reveals a phase transition from a rich-Te to a poor-Te surface as the annealing temperature increases
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 01
Keywords: Zinc Tellure; solar cells; structural properties; optoelectronics; semiconductors.